Holothoracic spinal epidural lipomatosis: Report of a rare presentation and review of literature - Maroua Hamadi Ben Salah; Mairi Ziaka (SAGE Open Medical Case Reports)
Spinal epidural lipomatosis refers to the abnormal accumulation of unencapsulated fat in the epidural space, pos s ibly associated with spinal canal narrowing and compression of adjacent nerve structures. Risk factors for spinal epidural lipomatosis include older age, male sex, obesity, and systemic corticosteroid use. While spinal epidural lipomatosis typically involves the thoracic or lumbosacral regions of the spinal cord, there are no published cases involving the entire thoracic cord. This report presents the first case of spinal epidural lipomatosis affecting the whole thoracic cord, highlighting the complexity of its diagnosis and management.